More than just contraception: the impact of the levonorgestrel-releasing intrauterine system on public health over 30 years. Issue 3 (29th January 2021) - Gemzell-Danielsson, Kristina; Kubba, Ali; Caetano, Cecilia; Faustmann, Thomas; Lukkari-Lax, Eeva; Heikinheimo, Oskari
Abstract : Universal access to sexual and reproductive health services is essential to facilitate the empowerment of women and achievement of gender equality. Increasing access to modern methods of contraception can reduce the incidence of unplanned pregnancy and decrease maternal mortality. Long-acting reversible contraceptives (LARCs) offer high contraceptive efficacy as well as cost-efficacy, providing benefits for both women and healthcare systems. The levonorgestrel-releasing intrauterine system (LNG-IUS) first became available in 1990 with the introduction of Mirena (LNG-IUS 20), a highly effective contraceptive which can reduce menstrual blood loss and provide other therapeutic benefits. The impact of the LNG-IUS on society has been wide ranging, including decreasing the need for abortion, reducing the number of surgical sterilisation procedures performed, as well as reducing the number of hysterectomies carried out for issues such as heavy menstrual bleeding (HMB). In the context of the COVID-19 pandemic, Mirena can provide a treatment option for women with gynaecological issues such as HMB without organic pathology, minimising exposure to the hospital environment and reducing waiting times for surgical appointments. Looking to the future, research and development in the field of the LNG-IUS continues to expand our understanding of these contraceptives in clinical practice and offers the potential to further expand the choices available to women, allowing them to select the option that best meets their needs.